2015
DOI: 10.1007/s00784-015-1692-0
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of postoperative pain after reciprocating or rotary NiTi instrumentation of root canals: a randomized, controlled clinical trial

Abstract: According to our findings and the results of the clinical trial, the occurrence of postoperative pain was low and similar between the reciprocating and rotary techniques during the time intervals assessed. These results are different from basic laboratory studies that affirm that the reciprocating techniques tend to promote more postoperative pain since extrusion of debris is greater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
102
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(112 citation statements)
references
References 32 publications
8
102
1
1
Order By: Relevance
“…Pasqualini, et al 7 (2015) evaluated the impact of rotary and reciprocating instrumentation on postoperative quality of life and concluded that reciprocating instrumentation affected postoperative quality of life to a greater extent than rotary instrumentation. Relvas, et al 10 (2015) and Kherlakian, et al 3 (2016) did not find significant difference between different reciprocating and rotary systems in terms of postoperative pain. These findings are not in concordance with our results.…”
Section: Discussionmentioning
confidence: 94%
“…Pasqualini, et al 7 (2015) evaluated the impact of rotary and reciprocating instrumentation on postoperative quality of life and concluded that reciprocating instrumentation affected postoperative quality of life to a greater extent than rotary instrumentation. Relvas, et al 10 (2015) and Kherlakian, et al 3 (2016) did not find significant difference between different reciprocating and rotary systems in terms of postoperative pain. These findings are not in concordance with our results.…”
Section: Discussionmentioning
confidence: 94%
“…Recently a couple of randomized controlled trials (RCT) have been published, that evaluated the pain reduction and/or the improvement in quality of life of single file systems (Kherlakian et al, 2016; Pasqualini et al, 2016; Relvas et al, 2016). In the first RCT (Kherlakian et al, 2016) two SF reciprocating systems (Reciproc (VDW, Munich, Germany) and WaveOne (Dentsply)) and one MF system (ProTaper Next (Dentsply)) were compared.…”
Section: Discussionmentioning
confidence: 99%
“…Also after treatment, pain rates on a categorized VAS 100 score were also very low and showed no significant differences between the systems. The second RCT (Relvas et al, 2016) compared one reciprocating SF system (Reciproc (VDW, Munich, Germany)) with a MF system (ProTaper (Dentsply)). Only asymptomatic teeth with apical periodontitis were included in the trial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations